Production of Biomass Briquette from Residual Bleaching Earth and Empty Palm Bunch - Naruebodee Srisang; Siriwan Srisang; Pitiwat Wongpitithawat; Korawit The-Eye; Kittipong Wongkeaw; Chakkarin Sinthoo (My University, 2017)
Bleaching earth (BE) and empty palm bunches (EPB) are residual materials in the palm oil production process. Inside BE consisted of copious oil quantities, in the same way, the EPB had the high heating value. These residual materials could be recycled to become the biomass briquettes (BB). Therefore, this work investigated the BB production at the different condition. The compression temperature was 150, 250 and 350°C. The compressive velocity was 30, 40 and 50 rpm. The mixture ratio by weight between BE and EPB was 30:70, 40:60, 50:50, 60:40 and 70:30. After production, the BB were examined the fuel properties, i.e., moisture content (MC), ash content (AC), the heating value (HV), the fixed carbon content (FC) and volatile matter content (VC). Experimental results showed the MC, HV, FC and VC diminished with the decrease of EPB quantity. The AC increased with the augmentation of BE content. The BB production rate increased with the compression velocity by it had the maximum production rate about 390 pieces per hour at the velocity of 50 rpm. Moreover, the increased velocity affected the diminution of HV, fixed carbon, moisture and volatile matter for some the mixture ratio and compression temperature. The alteration of compression temperature insignificantly affected the quantity of HV for some the mixture ratio and compression velocity. The BB production should be produced at the ratio of 30:70 combined with the compressive speed and temperature of 30 rpm and 250°C, respectively. This condition gave the high HV, the low moisture content corresponded with the standard of fuel properties, excepting, the quantity of ash and fixed carbon.
Keywords: Briquette; Residual oil; Carbon fibers; Heat of combustion; Thermochemical Biomass Conversion Processes